Body condition scoring in horses - Şeker, Ibrahim; Köseman, Abdurrahman (Ataturk Universitesi, 2016)
Body condition scoring is a system that measures level of fatness in the body of the horse. Body weight is a breed trait and it varies between the races. In addition, Horses exhibit variations in the optimum body condition in the yield functions because of individual differences. Today, the most commonly used system for determining the body condition is a 1-9 point scale. This system assess the body condition based on the level of the fatness behind the scapula, commissure of thoracal and lumbar area, around the tailhead, the ribs, withers, and neck. The level of condition varies by the feeding regime, and raising purpose. Body condition does not change in a short period of time; significant increases occur gradually. The condition is named based on the yield condition such as fattening performance, dairy, race, stock, pasture, and exhibition performance. Generally, high performance horses have lower body condition scores. Accurate determination of body condition allows the formulation of the required diet to create fat levels for the yield characteristic. The unbalanced feeding results in poor condition in speed, endurance, growth, fertility and body shape of horses, which are of significant importance for horse raising. In this review, information about the horse body condition is summarized.
Atlarda Beden Kondisyon Puanlamasi
Keywords: Condition; Horse; Performance; Scoring; Yield